Spontaneous bacterial peritonitis caused by Listeria monocytogenes: a rare infection with very high leukocyte counts in ascitic fluid-case report and review of the literature - Meurer, Amelie Johanna; Antoni, Christoph Helmer; Ebert, Matthias; Trimborn, Anna; Hirth, Michael (Clinics and research in hepatology and gastroenterology, 2023)
We present a rare case of Listeria monocytogenes-induced spontaneous bacterial peritonitis (SBP) in cirrhosis. Examination of the patient's peritoneal fluid revealed an extremely high leukocyte count. We suspect, that the patient belongs to 1% of individuals in which Listeria monocytogenes is part of the intestinal flora. Cephalosporins as empiric antibiotics have a Listeria gap. A combination of aminopenicillin and aminoglycoside is recommended. Therefore, early microbiological diagnosis from ascites and blood is essential. Listeria should be considered as a rare cause of SBP, especially in case of very high leukocyte count in peritoneal fluid or lack of response to empiric therapy.
Online verfügbar 26. April 2023, Artikelversion 29. April 2023
Gesehen am 16.06.2023